Exploring the influence of non-cognitive skills on academic achievement in STEM education: the case of Kazakhstan - Sultanova, Gulbakhyt; Shilibekova, Aidana; Rakhymbayeva, Zamira; Rakhimbekova, Assel; Shora, Nurym (Frontiers in Education, 2024)
Introduction This exploratory study delves into the relationships between non-cognitive skills and academic achievement within the unique context of STEM schools in Kazakhstan. Methods Survey data were collected from 109 teachers and 395 students at a STEM secondary school in Kazakhstan. Correlational, regression and path analyses were conducted to explore the relationship between non-cognitive skills and academic performance in Mathematics, Computer Science, Physics, and Chemistry classes. Results The results showed that out of the 26 skills, eight had a direct impact, 12 had an indirect impact, and six had no impact on academic achievement of students in the four STEM subjects. Discussion This study is the first to explicitly examine the impact of one group of non-cognitive skills on academic achievement of students in STEM subjects mediated by another group of these skills. Teachers are encouraged to integrate non-cognitive skill development into curricula, tailored to subject-specific needs. Policymakers can use findings to inform equitable skill development policies.